Prevalence of Use of Sports Trainer Services in Japanese High Schools: A Nationwide Survey - Yosuke Shibata; Yasunari Kurita; Kaho Morishita; Toshiyuki Ojima (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2024)
Objective: Sports trainers contribute to the safety of adolescent athletes. The status of sports trainer services (STS) that use a trainer-certified system and trainer perceptions differ among countries, and reports from different countries are needed to promote the global use of STS. This study aimed to determine the prevalence of STS and the reasons for its use in Japanese high schools. Method: A cross-sectional study was conducted in 2022. Participants were all club activity coaches from all high schools (around 70,000 coaches) in Japan. The primary outcome was the prevalence of STS use. We obtained information on the payment status when STS was used and the reasons they were not. Results: Of the 6045 coaches included, 10.5% used STS. Volunteer trainers comprised 29.9%, and if they were paid a fee, it needed to be more for a living. The most common reason for not using STS was